Estado e política cultural na Guiné-Bissau: uma análise da relação entre Estado e cultura no período democrático (1994-2020) - BUCAL, Vladimir (2023)
The relationship between the State and Culture is a subject of great relevance and academic interest, as cultural policies play a crucial role in the construction and consolidation of a country's identity. In the specific case of Guinea-Bissau, the appreciation of culture becomes even more relevant, considering the ethnic plurality and cultural diversity existing in its territory. This work is based on the premise that the relationship between the State and Culture in Guinea-Bissau has been strongly influenced by the formation process of the Guinean State throughout its history. Therefore, the aim of this dissertation was to analyze this relationship during the democratic period of Guinea-Bissau, which spans from 1994 to 2020. Based on this analysis, we sought to understand the challenges faced by the Guinean state in promoting and preserving national culture, as well as the strategies and measures adopted to strengthen the cultural identity of the country. The research adopted a bibliographic and documentary approach with a qualitative methodology. The object of study was the relationship between the State and Culture after independence, during the democratic period in Guinea-Bissau. This relationship manifests itself through the actions of different actors and social institutions, laws, and state and governmental policies in the formulation of public cultural policies. The methodological techniques applied included literature review and document analysis. The main objective of the research was to answer the central question: How does the relationship between the Guinean state and culture unfold during the democratic period? And what are the main determinants of this relationship? To support our analysis, we turned to classical and contemporary theories of culture and cultural politics, such as works on "Intellectuals and the Organization of Culture," "Common Customs: Studies on Traditional Popular Culture," "Culture and Materialism," "Culture and Socialism," and "Cultural Policies in Latin America." The theoretical framework was built based on authors such as Gramsci (1997, 1999), Williams (2003, 2007), Thompson (1998), CANCLINI (2001), Silva (2008, 2013), and others. The work points out that the relationship between the State and culture in Guinea-Bissau is complex and multifaceted, influenced by various historical, political, and social factors. Despite the challenges that this relationship presents, it also offers possibilities for the strengthening and appreciation of Guinean culture.